Curriculum 2013 in Double Major Class: the Teaching and Learning Process and the Problems - Faiza Hawa; Umniyyatul Makmuroh (ETERNAL (English Teaching Journal), 2016)
Indonesia has changed its curriculum for several times. The recent curriculum implemented is curriculum 2013 in which one of the purposes is to prepare productive ages to face ASEAN Economic Community (AEC). In curriculum 2013, one of the programs implemented by government for English subject is double major class. Therefore, this research aims to investigate the realization of  English teaching and learning process based on curriculum of 2013 double major class and find out the problems faced by students and teacher during the teaching and learning process. This study used descriptive qualitative design to answer the problems of the study. This study was conducted by using observation, interview and document as the instrument. The data of this study were taken from the observation, questionnaire and interview. The results of this stuudy show that; (1) the teacher only did observing, associating, and communicating steps in teaching English in double major class, (2) the problems faced by the students were on doing observing activity (66.7%), exploring activity (56.6%), associating (36.2%), and communicating (56.5%), while the problems faced by the teacher were there was no student asking on questioning step and limited time to look for information more in exploring step. From these findings the writers suggested the teacher to teach English in double major class based on curriculum 2013, to not dominate the class, to motivate students to be active in the class, and to give explanation to the students about the concept of curriculum 2013 and its implementation